2020
DOI: 10.1038/s41467-020-15294-w
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of hard pollen into soft matter

Abstract: Pollen's practically-indestructible shell structure has long inspired the biomimetic design of organic materials. However, there is limited understanding of how the mechanical, chemical, and adhesion properties of pollen are biologically controlled and whether strategies can be devised to manipulate pollen beyond natural performance limits. Here, we report a facile approach to transform pollen grains into soft microgel by remodeling pollen shells. Marked alterations to the pollen substructures led to environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 37 publications
0
68
0
Order By: Relevance
“…Self-organization of building blocks due to external stimuli is ubiquitous in most materials and all living organisms in nature. Inspired by this, a remarkable body of work has been performed to understand and emulate their response to temperature [1][2][3], pH [4][5][6] and light [7,8], enabling the controlled design of their structure assembly. Recent advances in polymer chemistry have led to the synthesis of various building blocks with complex architectures and functionalized properties.…”
Section: Introductionmentioning
confidence: 99%
“…Self-organization of building blocks due to external stimuli is ubiquitous in most materials and all living organisms in nature. Inspired by this, a remarkable body of work has been performed to understand and emulate their response to temperature [1][2][3], pH [4][5][6] and light [7,8], enabling the controlled design of their structure assembly. Recent advances in polymer chemistry have led to the synthesis of various building blocks with complex architectures and functionalized properties.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, pollenderived microcapsules have been developed as nonallergenic carriers to harness such advantageous properties as high mechanical strength, chemical stability, UV protection, and pathogen inhibition (51,52). Recently, we also demonstrated that it is possible to convert hard pollen grains into soft, stimuliresponsive microgel particles (53). However, the potential for developing other material forms based on natural, nonallergenic, and inexpensive pollen grains, thereby harnessing their unique functional capabilities and applications, has not been investigated to date.…”
mentioning
confidence: 99%
“…This is because the stiff pollen shell restricts the swelling of the pollen microgel. [ 31 ] These results indicate that two processes control the volume change of the pollen microgel. 1) The deprotonation of the carboxyl group in pectin acts a key role to provide the internal force for swelling/de‐swelling.…”
Section: Resultsmentioning
confidence: 91%
“…Recently, we developed the soapmaking‐like process to transform the pollen particles into the pollen microgels, which show great potential as a functional carrier for drug/protein delivery. [ 31 ] The pollen microgel particles also show pH‐ and ion‐ responsive swelling/de‐swelling behavior. The de‐esterification of pectin in the intine layer plays an important role in pollen gelation behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation